Kurikulum Merdeka: Analisis Asesmen Perkembangan Pendidikan Karakter di Sekolah Dasar - Sangadji, Harina (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to analyze how student development assessment and character education are implemented in the Independent Curriculum in Elementary Schools. The method used in this research is qualitative research with case studies in several elementary schools that use the independent curriculum in Central Ternate City District, Ternate City. Data was collected through observation, interviews and document analysis. The research results show that student development assessments focus more on individual progress and potential in the learning context. This approach also integrates character education in learning and assessment. Character education is not only through special subjects, but also in daily tasks and interactions at school. The Merdeka Curriculum in Elementary Schools applies a holistic approach to assessment that supports students' personal development. Thus, character education is an important part of this curriculum to help students develop positive values ​​and behavior in everyday life. The challenges that arise include the need for teacher training to integrate character education in learning and consistent assessment.